ByzRev 03.2021.006: Narrating Martyrdom. Rewriting Late-Antique Virgin Martyrs in Byzantium, translated with an introduction and notes by Anne P. Alwis: (Translated Texts for Byzantinists 9). Liverpool: Liverpool University Press 2020. - Samara, Demetra (The Byzantine Review, 2021)
Narrating Martyrdom. Rewriting Late-Antique Virgin Martyrs in Byzantium, translated with an introduction and notes by Anne P. Alwis (Translated Texts for Byzantinists 9). Liverpool: Liverpool University Press 2020. 224 pp. – ISBN: 978-1-789-62155-6 (£85.00)